Perception of Students Housing Complex in Malaysian Public University. Case Study: University of Malaya - Lim, Frederick.K.W; Aminuddin, Asrul (MAJ - Malaysia Architectural Journal, 2019)
Student housing, colloquially known as residential college is one of the most fundamental components of any tertiary academical institution, accommodating both undergraduates and postgraduates aside from carving memories and sense of nostalgia. The importance of student housing becomes apparent as it houses students who form the social backbone of the campus. University of Malaya is selected as the case study of this research because it has not been covered by any past researchers. Most of its student housing complexes were built in much earlier days for a different generation of varsity students as it is the oldest public university in Malaysia. It is therefore crucial to evaluate the perception of millennial students currently dwelling in these relatively old student housing complexes where their daily lifestyles and needs have modernly transformed. Students living in all twelve on-campus residential colleges of University of Malaya were selected as the sampling for this survey research. The final outcome of this research illustrates that students collectively have a feeling of moderate satisfaction towards their student housing. The only attributes that they are dissatisfied with is the sports and recreational facilities and the walkability as well as connectivity to the public transportation hub.